The assessment on the efficiency and effectiveness of commercial vehicles compulsory inspections at Petaling Jaya inspection centre / Mohd Zuhairi Mohd. Idris - Mohd. Idris, Mohd Zuhairi (1989)
There is an increase in the rates of commercial vehicles registered in Malaysia. Under the Road Traffic Ordinance, 1958; all commercial vehicles are required to be submitted for a periodic inspection at Road Transport Department Inspection Centre, available at every state. This study is aimed to assess the efficiency and effectiveness of inspections carried upon all commercial vehicles as conducted by the Road Transport Department of Selangor Darul Ehsan. In doing so, focus is made to the Road Transport Department state office situated at Petaling Jaya. Research is concentrated to this area as Petaling Jaya is the Commercial Vehicles Inspection Centre for both Federal Territory of Kuala Lumpur and Selangor Darul Ehsan. In compiling facts for this graduation exercise, it is observed that there are certain loopholes and weaknesses that need to be rectified by the relevant authorities, mainly pertaining to the safety, technicality and legality aspects of the mode of inspection as.well as to the whole system itself.